First report of Pentastomida in Asian water monitor lizard (Varanus salvator) in Bulung Hamlet, Jekulo District, Kudus Regency, Central Java, Indonesia - Yimer, Nurhusien; Nairiza, Muhammad Vistawan; Sudjarwo, Sri Agus; Lestari, Tita Damayanti (Svenska sallskapet for anthropologi och geografi, 2023)
Pentastomida is a parasite that can be found in reptiles, one of which is the Asian water monitor lizard. Several factors that support the life and development of parasites in Asian water monitor lizards are unhealthy food, individual behavior and a polluted environment. The aim of this research was to determine the Pentastomida species and the degree of pentastomiasis infection in the Asian water monitor lizard (Varanus salvator) in Bulung Hamlet, Jekulo District, Kudus Regency, Central Java. Pentastomide staining can use the Semichen-Acetic Carmine method. The Pentastomida species found in the Asian water monitor lizard (Varanus salvator) is Sambonia parapodum which has a yellowish-white color and its body looks segmented. The result of this research was the discovery of Pentastomida from the genus Sambonia, the Sambonia parapodum species in the nymph phase. It was found that 3 out of 100 Asian water monitor lizards were infected with Sambonia parapodum in the lungs of the Asian water monitor lizards. Competition between parasites could be one of the reasons why there are not many Pentastomida found even though the Asian water monitor lizards studied are wild animals. The number of Pentastomides found in the Asian water monitor lizard cannot always indicate the actual degree of infection if only the adult and larval phase parasites are counted in the lungs of the Asian water monitor lizard, so it is also necessary to calculate the number of worm eggs per gram of feces as well as examination of other tissues because Pentastomides can migrate to the lungs of the Asian water monitor lizard through various body tissues.